(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Financial planning is very crucial for achieving financial goals in life, one can anticipate the financial needs of the future and can ensure a smooth flow of funds at all times. The study is an eye-opener to the respondents as they got to know the pattern of their income and expenses. By saving the money spent on bad habits such as tobacco, smoking and drinking; they will be able to divert their income to return generating micro-investment avenues in future.